Hepatitis C screening and referral for further investigation and treatment in a tertiary care hospital - Gülşen İskender; Duygu Mert; Sabahat Çeken; Melike Bahçecitapar; Ayla Yenigün; Mustafa Ertek (Journal of Infection in Developing Countries)
Introduction: Hepatitis C virus infection is a major cause of cirrhosis and liver cancer worldwide. The knowledge of physicians about what should they do in case of any anti-HCV positivity in screening tests is of great importance. In this study the awareness and knowledge of physicians is evaluated by analyzing the rate of the referrals of anti-HCV positive patients to HCV RNA test and their treatment by different clinics.